EMSURE: energy and mobility for sustainable regions - António Gomes Martins (Outros títulos, 2015)
This book retraces the multidisciplinary research project EMSURE - Energy and Mobility for Sustainable Regions. Communicational articles - developed from a set of interviews with the researchers - aim to depict the wide range of disciplines that constitute the EMSURE. An encompassing framework that comprises such diverse areas as intelligent use of energy, sustainable mobility, buildings and energy efficiency, clean energy supply and assessment, and sustainable energy assessment, or planning for sustainability. Integrated in the Energy for Sustainability (EFS) initiative, of the University of Coimbra, EMSURE is established as a research project focused on multidisciplinary issues. Its main objectives include developing models, methodologies and technologies that enable the decision-makers and companies to promote a sustainable path within the Portugal Centre Region